Developing Education Media of Health Protocol utilizing Live Coloring using Augmented Reality Technology - Akbar Permana Putra; Priyanto Priyanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
The objective of the present study is to produce a learning media product of health protocol implementation to children entitled